Temperature-dependent charge-carrier dynamics in CH3NH3PbI3 Perovskite thin films - Milot, R; Eperon, G; Snaith, H; Johnston, M; Herz, L (Wiley, 2015)
The photoluminescence, transmittance, charge-carrier recombination dynamics, mobility, and diffusion length of CH3NH3PbI3 are investigated in the temperature range from 8 to 370 K. Profound changes in the optoelectronic properties of this prototypical photovoltaic material are observed across the two structural phase transitions occurring at 160 and 310 K. Drude-like terahertz photoconductivity spectra at all temperatures above 80 K suggest that charge localization effects are absent in this range. The monomolecular charge-carrier recombination rate generally increases with rising temperature, indicating a mechanism dominated by ionized impurity mediated recombination. Deduced activation energies Ea associated with ionization are found to increase markedly from the room-temperature tetragonal (Ea ≈ 20 meV) to the higher-temperature cubic (Ea ≈ 200 meV) phase adopted above 310 K. Conversely, the bimolecular rate constant decreases with rising temperature as charge-carrier mobility declines, while the Auger rate constant is highly phase specific, suggesting a strong dependence on electronic band structure. The charge-carrier diffusion length gradually decreases with rising temperature from about 3 μm at -93 °C to 1.2 μm at 67 °C but remains well above the optical absorption depth in the visible spectrum. These results demonstrate that there are no fundamental obstacles to the operation of cells based on CH3NH3PbI3 under typical field conditions. The photoconductivity in CH3NH3PbI3 thin films is investigated from 8 to 370 K across three structural phases. Analysis of the charge-carrier recombination dynamics reveals a variety of starkly differing recombination mechanisms. Evidence of charge-carrier localization is observed only at low temperature. High charge mobility and diffusion length are maintained at high temperature beyond the tetragonal-to-cubic phase transition at ≈310 K.